La mobilité d'un abbé au XVe siècle. Itinéraires et liens de communications de Thierry de Tuldel - Appelmans, Janick (Mobilité et stabilité chez les Prémontrés. Guerres, catastrophes et calamités. Actes officiels des 38e et 39e colloques du Centre d'Études et de Recherches Prémontrées. Amiens, 2012 - Troyes 2013, 2018)
Keywords: park

Les avatars des manuscrits médiévaux de l'abbaye de Parc - Van Balberghe, Emile (De Gulden Passer. Tijdschrift voor Boekwetenschap, 2010)
Keywords: park

L'Abbaye norbertine du Parc: un site unique du patrimoine à la lisière de la ville de Louvain - Van Lani, Stefan (Espaces sacrés, 2007)
Keywords: park

L'art de choisir ses objectifs: la stratégie politique de Thierry de Tuldel, abbé de Parc (1462-1494) - Appelmans, Janick (Abbatiat et abbés dans l?ordre de Prémontré, 2005)
Keywords: park

Thierry de Tuldel et les Prémontrés brabançons face à la commende (1470-1481) - Appelmans, Janick (Analecta Praemonstratensia, 2000)
During the later middle ages holding an abbey in commendam meant that is was granted to a secular clergyman, for example a bishop, a dean or a secular canon. At Saint Michael's abbey in Antwerp as well as in Tongerlo these commendators were influential members of the Burgundian court and high-ranking ecclesiastical officials. These princes of the church gave the duke more control over his clergymen and were in return provided with a substantially increased income. Ferry de Clugny made at Tongerlo in the years 1470-1471 the first successful intrusion in a Premonstratensian monastery in Brabant. His aspirations could be bought off by a lifelong rent. Diederik van Tuldel (1419-1494), the abbot of Park since 1462, undertook different diplomatic initiatives at the papal court in order to safeguard the Brabantine abbeys from more commendators. Despite many apostolic letters and guarantees his efforts were vain. In 1477 two bishops were appointed as the heads of the communities of Antwerp and Tongerlo. The reign of the commendatory prelates started at an ill fated moment, just a few weeks after the death of Duke Charles the Bold. The central government was not able any longer to support firmly the commendators in their struggle to obtain their offices and revenues. In contrast to the many collations of Benedictine abbeys in commendam the princes of the church faced well-informed and organized opponents. At several times the different Brabantine abbots gathered to discuss the state of affairs and took action against the commendators. Diederik van Tuldel and his fellow prelates knew every move of the secular abbots and their supporters. Therefore the abbot of Park could rely upon a network of trustful informers and skilled negotiators, including abbots and Premonstratensian delegates as well as merchants and church officials at the papal court. The last commendator finally resigned in 1481, but it had necessitated many funds to compel the secular abbots to desist from their prerogatives. Since his journey to Rome in 1475 Diederik van Tuldel had co-ordinated the defense of the liberties and rights of Saint Norbert's order and had taken care of the financial settlements. With the repetitive, but sometimes reluctant, consent of the order's general chapter the taille, a taxation within the order, was used. It lasted almost fifteen years before all the debts were reimbursed.
Keywords: park; 🇧🇪 belgium (general)

Le rôle des méthodes de laboratoire dans le recherche de la provenance de dinanderies médiévales. Application aux fonts baptismaux de Tirlemont, aux chandeliers des abbayes de Postel et de Parc des Musées Royaux d'Art et d'Histoire de Bruxelles et aux fonts baptismaux de Saint-Barthélemy à Liège - Martinot, L. (Académie royale de Belgique: Bulletin de la classe des beaux-arts, 1997)
Keywords: park

Les manuscrits médiévaux de l'Abbaye de Parc. Recueil d'articles - Balberghe, Emile van (Documenta et opuscula, 1992)
Keywords: park

Etude technologique des dinanderies coulées. 2: Les fonts baptismaux de Saint-Germain à Tirlemont (1149). 3: Le chandelier pascal de l'abbaye de Postel (XIIe s.). 4: Le chandelier pascal de l'abbaye de Parc (XIIIe s.) - De Ruette, Monique (Bulletin des Musées royaux d'art et d'histoire, 1987)
Keywords: park; postel

La cession des dîmes de Cella à l'abbaye du Parc - Delforge, A. (Cella, 1985)
Keywords: park

A propos de quelques manuscrits de l'abbaye de Parc conservés à la Bibliothèque de l'Université de Gand. - Van Acker, Kamiel G. (Archives et bibliothèques de Belgique / Archief- en bibliotheekwezen in België, 1974)
Keywords: park

Les critères de provenance des manuscrits de Parc - Van Balberghe, Emile (Contributions à l'histoire des bibliothèques et de la lecture aux Pays-Bas avant 1600: Studies over het Boekenbezit en Boekengebruik in de Nederlanden vóór 1600, 1974)
Keywords: park

Un manuscrit universitaire padouan à l'abbaye de Parc - Fransen, Gérard (Mélanges offerts à Pierre Andrieu Guitrancourt, 1973)
Keywords: park

Un catalogue des manuscrits de Parc rédigé sous Joseph II - Van Balberghe, Emile (Analecta Praemonstratensia, 1973)
Keywords: park

Deux manuscrits de Parc retrouvés - Van Balberghe, Emile (Analecta Praemonstratensia, 1970)
Keywords: park

Fragmenta Parcensia. A propos d'un fragment de la chronique dite de Saint Jérôme - Van Balberghe, Emile (Archives et bibliothèques de Belgique, 1970)
Keywords: park

Un relevé des manuscrits de Parc conservés à la Bibliothèque de l'Université de Louvain avant 1914 - Van Balberghe, Emile (Analecta Praemonstratensia, 1967)
Keywords: park

Extraits du nécrologie de l'Abbaye du Parc - Vander Linden, Albert (Revue belge de musicologie, 1951)
Keywords: park

L'abbaye norbertine du Parc-Le-Duc : huit siècles d’existence, 1129-1929 - Jansen, Joseph Evermode (Dessain, 1929)
Keywords: park

Les anciennes cures de Parc - Nols, Quirin (Analecta Praemonstratensia, 1929)
Keywords: park

Les chartes de fondation de l'abbaye du Parc - Versteylen, J. A. (Analecta Praemonstratensia, 1929)
Keywords: park

L'"Epistola reformatoria" du prieur de Bethléem Henri van der Heyden pour l'abbaye du Parc au XVe siècle - Heyden, Henri van der (Imprimerie de l'abbaye, 1927)
Keywords: park

Thierry van Tuldel et la commende en Brabant. 1470-1490 - Erens, Ambrosius (Analecta Praemonstratensia, 1925)
Keywords: park; 🇧🇪 belgium (general)

Une élection abbatiale au XVe siècle. Thierry de Thulden, abbé du Parc (1462) - Waefelghem, Raphaël van (Mélanges d'histoire offerts à Charles Moeller : à l'occasion de son jubilé de 50 années de professorat à l'Univ. de Louvain, 1863-1913, 1914)
Keywords: park

Les cartulaires de l'abbaye du Parc - Waefelghem, Raphaël van (Analectes de l'Ordre de Prémontré, 1909)
Keywords: park

Le Nécrologe de l'abbaye du Parc - Waefelghem, Raphaël van (Analectes de l'Ordre de Prémontré, 1908)
Keywords: park

Notitia relatant quelques une des premières donations à l'abbaye du Parc - Nélis, Hubert (Analectes de l'Ordre de Prémontré, 1906)
Keywords: park

Recherches historiques sur l'ancienne abbaye de Parc - Raymaekers, F.J. (Revue catholique: Recueil Religieux, Philosophique, Scientifique, Historique et Littéraire, 1858)
Keywords: park